(3GdHGgQ aj eYQaI GdGMLGQ hGdLhGgQs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg CeG HYO aEfj PGcQ aj gPG GdcJGH efGaY GdGMLGQ hGdfHGJ hGdMjhGf aef Pdc MLQ jSej GdUfhfh bGd CQSWh Gfg UGdM dOaY GdHQbGf jhLO aj YT GdNWGa s
(3BNQgG (B:s
(3hef Hg MH GdbQY jNdW QeGOg, hgPG GdTYQ s
(3HgG fXGe GdJYbjHIs
(3hajg GjVkG NhGU GdfHGJGJ hGdMjhGfGJ efbhd ef YLGFH GdeNdhbGJs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs